ANALYSIS OF THE FINANCIAL LITERACY ON ECONOMIC GROWTH IN INDONESIA - Lubis, Anggi Permata Rizky; Rangkuty, Dewi Mahrani; Pane, Sanusi Gazali (PT. Arsil Reka Engineering, 2024)
The higher a person's financial literacy, the greater the level of utilisation of financial products and services. Expenditure management can take advantage of financial literacy so that it can maintain finances in meeting its needs, and good financial conditions will reflect economic growth that continues to increase. The purpose of this study is to determine the effect of financial literacy on economic growth with indicators such as balance of payments, investment, total loans, savings, money supply and interest rates. With the vector autoregression (VAR) analysis method which results in that the balance of payment variable has a mutual effect on investment. Then investment and economic growth are also influenced by savings and money supply and affect interest rates and the amount of loans. So as to limit the risk of financial literacy failure in the financial system, it is necessary to increase financial risk with product innovation in the financial sector.